Hello, Kristin!
I'm still
guessing what the problems look like . . .
\(\displaystyle 1)\;\;-4x\sqrt{xy}\,-\,x\sqrt{xy}\)
\(\displaystyle \text{Answer: }-5x\sqrt{xy}\) . . . is that correct? . [ . . . yes!
\(\displaystyle 2)\;\;3\sqrt{12}\,-\,2\sqrt{108}\)
Remember how to "simplify" square roots?
. . Recall that:
.\(\displaystyle \sqrt{12}\,=\,\sqrt{4\cdot3}\,=\,\sqrt{4}\cdot\sqrt{3}\,=\,2\sqrt{3}\)
. . and that:
.\(\displaystyle \sqrt{108}\,=\,\sqrt{36\cdot3}\,=\,\sqrt{36}\cdot\sqrt{3}\,=\,6\sqrt{3}\)
We have:
.\(\displaystyle 3\cdot\sqrt{12}\:-\:2\cdot\sqrt{108}\)
. . . . . . . . . . . \(\displaystyle \downarrow\;\;\;\;\;\;\downarrow\)
. . . . . . . . . \(\displaystyle 3\cdot\overbrace{2\sqrt{3}} \:-\:2\cdot\overbrace{6\sqrt{3}}\;=\;6\sqrt{3}\,-\,12\sqrt{3}\;=\;-6\sqrt{3}\)
\(\displaystyle 3)\;\;\sqrt{x^2}\,=\,9\)
Square both sides:
.\(\displaystyle (\sqrt{x^2})^2\:=\:9^2\)
and we have:
.\(\displaystyle x^2\:=\:81\)
Therefore:
.\(\displaystyle x\:=\:\pm9\)